Model Pembelajaran Contextual Teaching and Learning: Meta Analisis terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Cahayati, Reni; Hasanuddin, Hasanuddin (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2025)
The purpose of this research is to analyze the effectiveness of the CTL learning model in improving students' KPMM using a meta-analysis approach. Through the analysis of 15 relevant articles from various educational levels within the 2013–2024 timeframe, it was found that the implementation of the CTL model has a significant positive impact on the improvement of KPMM and helps students develop self-confidence and critical thinking skills. Although the majority of studies show positive effects, challenges in the implementation of this model, particularly related to the use of traditional teaching methods by some teachers, need to be addressed. Additionally, it is recommended that educational institutions enhance teacher training, design authentic assessments, and integrate mathematical concepts with real-life contexts. These findings affirm that the CTL model has great potential in enhancing the effectiveness of mathematics learning and encourage further research to explore innovative approaches in mathematics teaching.